2019
DOI: 10.3233/wor-182822
|View full text |Cite
|
Sign up to set email alerts
|

An ergonomic intervention to relieve musculoskeletal symptoms of assembly line workers at an electronic parts manufacturer in Iran

Abstract: BACKGROUND: Prolonged, awkward postures among assembly line workers can lead to work-related musculoskeletal disorders (WMSDs). OBJECTIVE: This study determined the prevalence of WMSDs and ergonomic risk factors among assembly line workers at an electronic parts manufacturer, and introduced a low-cost ergonomic intervention. METHODS: Data were gathered by means of a questionnaire. The Rapid Upper Limb Assessment (RULA) technique was used to determine ergonomic risk factors. A low-cost intervention, designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The prevalence of WMSs during the 12 months prior to the study in some body regions of the studied population, including shoulders, wrists/hands, upper back, lower back, knees, and ankles/feet, was higher than that reported among other Iranian working groups, comprising healthcare providers [23], hospital attendants [24], workers in orthotic and prosthetic workshops [25], office workers [23,[26][27][28], assembly line workers [29], petrochemical industry workers [30], manufacturing industries workers [23], and agricultural workers [31].…”
Section: Prevalence Of Wmssmentioning
confidence: 99%
“…The prevalence of WMSs during the 12 months prior to the study in some body regions of the studied population, including shoulders, wrists/hands, upper back, lower back, knees, and ankles/feet, was higher than that reported among other Iranian working groups, comprising healthcare providers [23], hospital attendants [24], workers in orthotic and prosthetic workshops [25], office workers [23,[26][27][28], assembly line workers [29], petrochemical industry workers [30], manufacturing industries workers [23], and agricultural workers [31].…”
Section: Prevalence Of Wmssmentioning
confidence: 99%
“…It has been found that assemblers spend most of their working time with a position in which their neck has been bent forward or backward. In the studies of Charles [ 14 ], Grieco [ 15 ], Sun Yan [ 16 ], Aghilinejad [ 17 ], Daneshmandi [ 18 ], and Maimaiti [ 19 ], it has been asserted that the musculoskeletal disorders are more prevalent in the neck and shoulders of assemblers.…”
Section: Discussionmentioning
confidence: 99%
“…It is a fact that automotive assembly line workers frequently perform repetitive movements in static positions, which can explain the lower limbs reference. Other papers have advanced back, neck, shoulder, and leg as the anatomical areas with more reported symptoms [ 2 , 3 , 5 , 41 ]. On the other hand, the upper limb symptoms reported during 6 months by our population are slightly lower when comparing with what has been advanced in other studies in industry workers [ 7 , 23 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Highly repetitive work (the same movement two to four times a minute or in cycles below 30 seconds [ 1 ]), manual force application, and awkward postures are present in assembly line work [ 2 , 3 ]. These are some of the occupational hazards associated to work-related upper limb musculoskeletal disorders (WRULMSDs) [ [2] , [3] , [4] , [5] ], especially of the neck and upper limb and the most common in assembly lines [ 6 ].…”
Section: Introductionmentioning
confidence: 99%